BAWAL FISH GROWTH PATTERN CAUGHT BY FISHERMEN IN TPI KUALA LANGSA LANGSA LANGSA CITY - Dini Fitria; Abdul L Mawardi; Indah Indah (Universitas Islam Negeri Ar-Raniry, 2022)
The waters of the East Coast sea of Aceh have promising fishery potential with an abundance of fish species. a fish with a high selling value is the bawal fish species. Sea bawal fish in TPI Kuala Langsa is an important fishery commodity that has a high protein content and its marketing includes domestic and exports, especially in Asia, thus encouraging fishermen to make over fihing. The study was conducted from December to January 2022. The methods in this study are descriptive methods and observation techniques. The results showed that the bawal species caught by fishermen at TPI Kuala Langsa Kota langsa as many as 2 species, namely white bawal (Pampus argentus) and black bawal (Parastromateus niger). The long frequency distribution on white carries ranges from 156-307 mm class and black bawal in class 154-378 mm. The growth pattern of white bawal in December with a value of b is 1.143 while in January with a value of b is 1.4569 and black bawal in December with a value of b of 1.5484 while in January with a value of b of 1.8233.